A new horizon in European sports law: the application of the EU state aid rules meets the specific nature of sport - Garcia, B; Vermeesch, A; Weatherill, S (Taylor and Francis, 2017)
recent influx of cases on state aid granted to sport undertakings in several EU Member States has brought to the fore the debate on the interpretation and application of this particular competition policy provision to the sports sector. This article reviews the recent Commission decisions on state aid in order to discuss the extent to which a coherent approach by the Commission can be found. The article notes the Commission’s readiness to treat support for sports infrastructure as an aspect of “state responsibility”, which tends to generate a positive assessment under EU state aid law and contrasts this with its critical scrutiny of financial support granted to ailing sports clubs, where the Commission has been more cautious. It also discusses the wider political and policy implications of the application of European state aid rules to sport. Its core inquiry is how convincing is the case that sport deserves to be treated as a special case, distinct from other areas of economic activity?